It’s a Wonderful Life:Representations of the Small Town in American Movies - Thomas Halper- Douglas Muzzio (European Journal of American Studies)
As America thinks about itself – its values, its roots, its evolution – a central theme is the small town, cherished as a wholesome refuge, warm and friendly, and derided as dull and provincial, intrusive and nosy. From their inception, movies have served as one of the society’s principal means of discourse on the topic, generally lauding small towns during the silent era and the Depression, becoming steadily more critical after the war, and more recently depicting them as faded anachronisms. The reel small town is compared to the real small town, and Simmel’s notion of the plight of the individual in modern society provides an organizing principle.